The Module of Power Point Optimization Training SDL Based to Improve the Teacher’s Competence in Developing Learning Media - Pilendia, Dwitri; Amalia, Shabrina (JPI (Jurnal Pendidikan Indonesia), 2020)
This study aims to express the effectiveness of module development of power point optimizing training as a learning media. The module developed has several excellences such as the material presentation presented focusing on how to make a good learning media, started from the opening part, material, evaluation, references, completed with self assessment and presentation of Self Directed Learning (SDL) based material which eases the teacher to study independently. The type of this research was R&D with 4D model. based on the observation result found that predominantly the teachers did not acquire power point yet. Based on the result of N-Gain test on pre-test and post-test score shows that the average score of N-Gain is > 0,70 (high category). The result of self assessment on each meeting shows that 75% teachers have achieved score 70. Based on this data, it can be concluded that the module being developed is included into effective category in improving the teachers’ competence especially in making technology based learning media.